2018
DOI: 10.1504/ijsmm.2018.091753
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework to understand the creation of athlete brand and its implications

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 21 publications
2
28
0
14
Order By: Relevance
“…Also, this study discussed the less popular sport athletes in the branding context. Past studies have identified that the types, popularity, and nature of sport demonstrated different effects on brand equity of athletes (Hasaan et al, 2018). In this context, the current study provides a significant contribution to the literature as well as practitioners who manage athlete branding.…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…Also, this study discussed the less popular sport athletes in the branding context. Past studies have identified that the types, popularity, and nature of sport demonstrated different effects on brand equity of athletes (Hasaan et al, 2018). In this context, the current study provides a significant contribution to the literature as well as practitioners who manage athlete branding.…”
mentioning
confidence: 73%
“…The central tenet that contributes to this line of athlete branding literature is customer-based brand equity, mainly focusing on perceptions that customers have towards the target athletes (Arai et al 2014;Biscaia, Correia, Ross, Rosado, & Maroco, 2013;Hasaan et al 2018;Keller, 1993). Other researchers also argued that awareness and prestige among fans are essential for athletes to be considered as a brand (Arai et al 2014;Hasaan et al 2018). Lastly, incorporating the media influence is particularly important to understand athlete branding as consumers are strongly influenced by media (Parmentier & Fischer, 2012).…”
Section: The Process Of Athlete Brandingmentioning
confidence: 99%
See 3 more Smart Citations